Perceived relative wealth and risk taking - Fehr, Dietmar; Reichlin, Yannick (CESifo working papers, 2021)
We show that perceptions of relative rank in the wealth distribution shape individuals' willingness to take risks. Using a representative large-scale survey, we manipulate perceptions of relative standing by randomly varying response categories when asking respondents about their wealth level. Respondents who are induced to perceive their relative position as low display more tolerance towards risk in a subsequent incentivized lottery task. This effect is mainly driven by individuals who more firmly believe that life outcomes are beyond their control. This interaction between risk preferences and underlying beliefs spotlights the benefits of incorporating personality traits into economic analysis.
Keywords: Graue Literatur